Validation of the Persian version of the dysphagia handicap index in patients with neurological disorders - Barzegar-Bafrooei, Ebrahim (Iran J Neurol, 2016)
Background: Dysphagia as a common condition affecting many aspects of the patient’s life. The Dysphagia Handicap Index (DHI) is a reliable self-reported questionnaire developed specifically to measure the impact of dysphagia on the patient’s quality of life. The aim of this study was to translate the questionnaire to Persian and to measure its validity and reliability in patients with neurogenic oropharyngeal dysphagia. Methods: A formal forward-backward translation of DHI was performed based on the guidelines for the cross-cultural adaptation of self-report measures. A total of 57 patients with neurogenic dysphagia who were referred to the neurology clinics of Tehran University of Medical Sciences, Iran, participated in this study. Internal consistency reliability of the DHI was examined using Cronbach’s alpha, and test-retest reliability of the scale was evaluated using intraclass correlation coefficient (ICC). Results: The internal consistency of the Persian DHI (P-DHI) was considered to be good; Cronbach’s alpha coefficient for the total P-DHI was 0.88. The test-retest reliability for the total and three subscales of the P-DHI ranged from 0.95 to 0.98 using ICC. Conclusion: The P-DHI demonstrated a good reliability, and it can be a valid instrument for evaluating the dysphagia effects on quality of life among Persian language population.